Experimental model to study the effect of nicotine in a random skin flap, in the rat - Gomes,Heitor Carvalho (2004)
Presentation of an experimental model to study the effect of nicotine in a random skin flap, in the rat. Adult rats of the same lineage are exposed to nicotine for seven days in the preoperative period. After the preoperative period, the animals are anesthetized and a dorsal random pattern skin flap, cranially based is elevated. On the seventh postoperative day, the rats are anesthetized and the percentages of distal necrosis in the flaps are determined. After that, excision of skin fragments for biochemical analysis is possible. Blood samples may be collected by decapitation.